PORTUGUESE IMPERIAL BUILDING IN THE KOTTE KINGDOM OF SRI LANKA AS A REFLECTION OF 16TH CENTURY INTERNATIONAL LAW - Punsara Amarasinghe (Lampung Journal of International Law, 2023)
The colonial nature of international law has been a moot point in legal academia, which univocally suggests international law as an imperial instrument. Given these exergies, the question that this paper seeks to examine is how Portuguese encounters in the 16th century Sri Lanka reflects the seeds of international legal system dominated by European interests. The policy espoused by the Portuguese in Sri Lanka during their encounters with the Kotte kingdom raise the initial examples of unequal treaties, exclusion of sovereignty and the adoption of “puppet rulers”. This paper makes a critical inquiry in examining these elements parallel to the development of 16th century international law.